A new species of Glyptapanteles (Hymenoptera: Braconidae: Microgastrinae), a larval parasitoid of Elymnias hypermnestra (Linnaeus) (Lepidoptera: Nymphalidae), along with some new host records of parasitoids from Peninsular India - Gupta, Ankita; Pereira, Blaise (Zootaxa, 2012)
A new species, Glyptapanteles hypermnestrae Gupta and Pereira, is described from Maharashtra, India, and comparedwith closely allied species. This new species was bred from parasitized larvae of Elymnias hypermnestra (Linnaeus) (Lep-idoptera: Nymphalidae). In addition to this, two hymenopteran parasitoids, Apanteles folia Nixon (Braconidae: Microgas-trinae) and Brachymeria indica (Krausse) (Chalcididae), are for first time reported parasitizing larvae of Arhopalaamantes (Hewitson) (Lepidoptera: Lycaenidae) and pupae of Pareronia valeria (Cramer) (Lepidoptera: Pieridae) respectively.